Geochemistry and Sm–Nd isotopic composition of the Imiter Pan-African granitoids (Saghro massif, eastern Anti-Atlas, Morocco): Geotectonic implications. (March 2017) - Baidada, Bouchra; Cousens, Brian; Alansari, Abdelkhalek; Soulaimani, Abderrahmane; Barbey, Pierre; Ilmen, Said; Ikenne, Moha
Abstract: The Imiter inlier (eastern part of the Moroccan Anti-Atlas) is located on the northwestern border of the West African Craton (WAC) and exhibits a range of Pan-African granitoids. Three massifs that crosscut the Imiter Saghro Group were targeted in this work: the Igoudrane granodiorite, Bou Teglimt granodiorite and Bou Fliou granite. We present here additional geochemical analyses (major and trace elements) and Sm-Nd isotopic data, which define two distinct groups: (i) the Igoudrane massif (677 Ma) and (ii) the Bou Teglimt granodiorite (576 Ma) and the Bou Fliou granite (550 Ma). Geochemical data confirm the calc-alkaline signature of the studied granitoids. Both groups of granitoids are slightly peraluminous and show strong negative anomalies in Nb, Ta and Ti in multi-element plots normalized to the primitive mantle. The granitoids have low 143 Nd/ 144 Nd initial ratios (0.5116–0.5117), with TDM model ages ranging from 1.73 to 1.52Ga. The εNd(t) values are negative, decreasing from the Igoudrane samples (−1.1 to −3.1) to the Bou Teglimt granodiorite (−3.0 to −3.3) and Bou Fliou (−4.2 to −4.8). All these data suggest a mixed magmatic origin involving a juvenile mantle source and an old, at least Paleoproterozoic crust. Given Mesoproterozoic rocks are lacking or very scarce in the Anti-Atlas, these results confirm the existence of an old cratonic basement beneath the eastern Anti-Atlas, and therefore suggest that the northern border of the West African Craton must be placed further to the north, as suggested by previous work in this region. Highlights: Geochemical data confirm the calc-alkaline signature of the studied granitoids. The post-collisional magmatism in the Imiter inlier is highly diverse in ages and compositions, indicating multi-stages and various sources melting. The results of Sm-Nd isotopes suggest a mixture of mantle and crust sources. The TDM model ages of 1.42–1.75 Ga indicate a magma source that was comprised of pre-Pan-African crustal rocks.